Diagnostic Accuracy of Cone-Beam Computed Tomography and Periapical Radiography in Internal Root Resorption - Madani, Zahrasadat; Moudi, Ehsan; Bijani, Ali; Mahmoudi, Elham (Iranian Endodontic Journal, 2016)
Introduction: The aim of this study was to compare the diagnostic value of cone-beam computed tomography (CBCT) and periapical (PA) radiography in detecting internal root resorption. Methods and Materials: Eighty single rooted human teeth with visible pulps in PA radiography were split mesiodistally along the coronal plane. Internal resorption like lesions were created in three areas (cervical, middle and apical) in labial wall of the canals in different diameters. PA radiography and CBCT images were taken from each tooth. Two observers examined the radiographs and CBCT images to evaluate the presence of resorption cavities. The data were statistically analyzed and degree of agreement was calculated using Cohen’s kappa (k) values. Results: The mean±SD of agreement coefficient of kappa between the two observers of the CBCT images was calculated to be 0.681±0.047. The coefficients for the direct, mesial and distal PA radiography were 0.405±0.059, 0.421±0.060 and 0.432±0.056, respectively (P=0.001). The differences in the diagnostic accuracy of resorption of different sizes were statistically significant (P<0.05); however, the PA radiography and CBCT, had no statistically significant differences in detection of internal resorption lesions in the cervical, middle and apical regions. Conclusion: Though, CBCT has a higher sensitivity, specificity, positive predictive value and negative predictive value in comparison with conventional radiography, this difference was not significant. Keywords: Cone-Beam Computed Tomography; Periapical Radiography; Root Resorption